Efficacy of psychological interventions for irritable bowel syndrome: A protocol for systematic review and meta-analysis. Issue 10 (11th March 2022) - Yao, Fei; Wu, Xutao; Zhao, Huacheng; Gan, Chun
Abstract: Background: Guidelines for the management of irritable bowel syndrome (IBS) recommend that psychological therapies should be considered, but their relative efficacy is unknown. We performed a protocol for systematic review and meta-analysis to try to resolve this uncertainty. Methods: Two individual researchers conducted the platform searches on Ovid Medline In-Process & Other Non-Indexed Citations, Ovid MEDLINE, Ovid EMBASE, Ovid PsycINFO, Ovid Cochrane Central Register of Controlled Trials, Ovid Cochrane Database of Systematic Reviews, and Scopus from inception to February 2022. Systematic review and meta-analysis of the data will be performed in STATA13.0 software according to the preferred reporting items for systematic reviews and meta-analyses protocols guidelines. Two authors independently performed the literature searching, data extraction, and quality evaluation. Risk of bias was assessed using the Cochrane Risk of Bias Tool for randomized controlled trials. Results: A synthesis of current evidence of psychological interventions for IBS will be provided in this study. Conclusion: This result will provide a comprehensive analysis and synthesis to inform practitioners and policy makers about the effectiveness of psychological interventions for patients with IBS.